Effects of COVID-19 on maternal anxiety and depressive disease: a literature review - I. Mappa; F. A. Distefano; G. Rizzo (Сеченовский вестник)
The coronavirus SARS-CoV-2 (COVID-19) infection is a public health emergency of international concern. Pandemics pose a challenge to psychological resilience and can have an adverse impact on mental health. The impact of the ensuing social isolation and loneliness imposed by quarantine along with the worries about the risks of the infection and its economic fallout would appear likely to affect the mental health of the population. It has been reported that women are more likely to experience anxiety and depression symptoms during COVID-19 than men. COVID-19 pandemic had a profound impact on the level of anxiety and depression of pregnant women according to their basal level and pregnancy characteristics. Antenatal mental disorders may be a risk factor for maternal mental health problems such as an increased likelihood of postnatal depression and adverse obstetric and developmental outcomes. Effective coping strategies are associated with better psychological wellbeing during the COVID-19 pandemic, including reduced anxiety and depression. The increased risk of mental disorders due to COVID-19 requires policies to be developed to address prenatal and postpartum care to promote maternal-child wellbeing outcomes.